2010
DOI: 10.1002/dys.410
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia and explicit long‐term memory

Abstract: The reduced verbal long-term memory capacities often reported in dyslexics are generally interpreted as a consequence of their deficit in phonological coding.The present study was aimed at evaluating whether the learning deficit exhibited by dyslexics was restricted only to the verbal component of the long-term memory abilities or also involved visual-object and visual-spatial domain. A further goal of the present study was to investigate the predictive value of non-verbal long-term memory abilities with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…For example, Nelson and Warrington (1980) reported normal LTM functions in developmental dyslexia (see also Bell, 1990). In contrast, a recent Italian study reported specific LTM impairments in dyslexics (Menghini et al, 2010; see also Watson and Willows, 1995). Probably, these heterogeneous findings are due to the fact that those studies did not explicitly address resolution issues in LTM, that is, the ability to acquire highly detailed representations of visual objects.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, Nelson and Warrington (1980) reported normal LTM functions in developmental dyslexia (see also Bell, 1990). In contrast, a recent Italian study reported specific LTM impairments in dyslexics (Menghini et al, 2010; see also Watson and Willows, 1995). Probably, these heterogeneous findings are due to the fact that those studies did not explicitly address resolution issues in LTM, that is, the ability to acquire highly detailed representations of visual objects.…”
Section: Introductionmentioning
confidence: 84%
“…The core result of our study is that while the overall amount of LTM errors was comparable between groups, dyslexics showed a significantly greater portion of detail-related memory errors, suggesting a specific spatial resolution deficit in VLTM of dyslexic children. Previous studies on the role of VLTM in dyslexia only yielded mixed results (ranging from normal to impaired LTM functions; see Nelson and Warrington, 1980; Bell, 1990; Watson and Willows, 1995; Menghini et al, 2010), probably because these studies did not specifically address the issue of VLTM resolution, which may be of utmost importance regarding the storage of visual word forms in the mental lexicon.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identifi ed defi cits in a sub-domain of executive functioning in both children and adults with dyslexia (Altemeier, Abbott, & Berninger, 2008 ;Brosnan, Demetre, Hamill, Robson Shepherd et al, 2002 ;Helland & Asbjornsen, 2000 ;Horowitz-Kraus, 2014 ;Gooch, Snowling, & Hulme, 2011 ;Kraus & HorowitzKraus, 2015 ;Menghini, Carlesimo, Marotta, Finzi, & Vicari, 2010, Reiter, Tucha, & Lange, 2005Tiffi n-Richards, Hasselhorn, Woerner, Rothenberger, & Banaschewski, 2008 ). One of the only ERP studies to examine the impairment of EF in individuals with dyslexia (Horowitz-Kraus, 2014 ) used the Wisconsin card-sorting task, which is a task that encompasses several EF domains.…”
Section: Dyslexia and Executive Functioningmentioning
confidence: 97%
“…Dyslexia can be deconstructed into underlying core components, known as “intermediate phenotypes”. These include deficits in phonological processing (Kovelman et al, 2012; Melby-Larvag, Lyster & Hulme, 2012; Peyrin et al, 2012), short-term and/or working memory (Beneventi et al, 2010; Gathercole et al, 2006; Menghini et al, 2010), visuospatial attention (Franceschini, 2012; Gabrieli & Norton, 2012), and rapid auditory processing (Cohen-Mimran & Sapir, 2007; Fitch & Szalkowski, 2012; Hamalainen, Salminen & Leppanen, 2013). Other behavioral deficits that have been specifically associated with dyslexia include naming speed, motor functioning and visual processing of motion (Denckla & Rudel, 1976; Liao et al, 2015; Capellini, Coppede & Valle, 2010; Olulade, Napeliello & Eden, 2013).…”
Section: Introductionmentioning
confidence: 99%